Effect of Magnesium Sulfate on Intraoperative Hemodynamics, Anesthetic Consumption, and Postoperative Pain in Elective Laparoscopic Cholecystectomy - Huda ALhrare; Mohamed Bellael; Moad Ben Taher (AlQalam Journal of Medical and Applied Sciences, 2025)
Laparoscopic Cholecystectomy (LC) is the gold standard treatment for gallstones; however, postoperative pain and hemodynamic fluctuations remain concerns. Magnesium sulfate (MgSO₄) has potential analgesic, muscle relaxant, and hemodynamic stabilizing properties. This study aims to evaluate the effects of MgSO₄ on intraoperative hemodynamics, anesthetic consumption, and postoperative pain in patients undergoing elective LC. A prospective study was conducted on 40 ASA I-II patients scheduled for elective LC at Al Wahda Hospital, Derna, between September 2024 and January 2025. Patients were randomly assigned into two groups: Magnesium group (20) received 50 mg/kg IV MgSO₄ in 100 ml normal saline at induction of anesthesia, and the control group (20) did not receive. Hemodynamic parameters (blood pressure and heart rate) were recorded at induction, maintenance, and recovery. Total intraoperative fentanyl and rocuronium consumption were measured. Postoperative pain was assessed using the Visual Analog Scale (VAS). Patients who received MgSO₄ had significantly lower intraoperative fentanyl consumption (85.0 ± 32.84 µg vs. 125.0 ± 34.4 µg, p=0.001) and rocuronium dose (61.5 ± 13.28 mg vs. 65.0 ± 24.86 mg, p=0.582). Hemodynamic stability was better in the magnesium group, with a significant reduction in systolic and diastolic blood pressure during maintenance (p<0.05). Postoperative pain scores were lower in the magnesium group, with reduced tramadol consumption. Perioperative administration of MgSO₄ in LC reduces intraoperative anesthetic consumption, stabilizes hemodynamics, and improves postoperative pain control without increasing adverse effects. Further studies with larger sample sizes are recommended.